Employee Recognition and Performance: A Field Experiment - Christiane Bradler; Robert Dur; Susanne Neckermann; Arjan Non (Institute for the Study of Labor (IZA), 2014)
This paper reports the results from a controlled field experiment designed to investigate the causal effect of unannounced, public recognition on employee performance. We hired more than 300 employees to work on a three-hour data-entry task. In a random sample of work groups, workers unexpectedly received recognition after two hours of work. We find that recognition increases subsequent performance substantially, and particularly so when recognition is exclusively provided to the best performers. Remarkably, workers who did not receive recognition are mainly responsible for this performance increase. Our results are consistent with workers having a preference for conformity and being reciprocal at the same time.
Keywords: C93; M52; 330; employee motivation; recognition; reciprocity; conformity; field experiment